In-vitro culture and developmental changes of yellow stem borer Scirpophaga incertulas Under Different microclimate conditions on the MR297 rice variety - Idris Dauda,; Norida Mazlan,; Anis Syahirah Mokhtar,; Nor Azura Husin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Scirpophaga incertulas (Walker) (Lepidoptera: Crambidae), also called the Yellow Stem Borer, is a major prominent insect pest in rice production that results in substantial crop losses. Due to climate change, the infestation of S. incertulas has become more serious. This study was carried out between March and April 2022 to investigate the in-vitro culture and developmental changes of S. incertulas under different microclimates on the MR297 rice variety. The experiment was set up in a completely randomized design, and the data on the mean developmental stages of the lengths and widths were measured. A student's t-Test was used to compare the mean differences in lengths and widths of the developmental changes in instar larvae and pupae of S. incertulas in the two microclimate conditions. Multi-linear regression analysis was used to correlate the relationship between the microclimate factors and the developmental changes in S. incertulas on the MR297 rice variety. Data were analyzed using SPSS (version 20) and R studio (version 4.2.1) software. The correlation analysis of the data showed a positive relationship between the developmental changes in lengths and widths of S. incertulas for the laboratory and field microclimatic conditions using the MR297 rice variety. This study successfully examined the in-vitro culture and developmental changes of S. incertulas under different microclimates, from egg hatching to the adult's emergency.